Research on compound twill generation algorithm based on moving matrix - Xiaobo Yang (PLoS ONE, 2025)
To further enhance the authenticity of yarn simulation, we propose an algorithm for generating Compound Twills based on a moving matrix. Firstly, the key to designing composite twill is to determine the fly count. When the fly count of the twill is constantly changing, a composite twill can be obtained. Therefore, by utilizing the constantly changing characteristics of the fly count of the composite twill, a composite twill movement matrix model is established. Then, using this model, the appearance shape of complex fabrics can be reconstructed starting from simple composite twill. Finally, the Hilbert curve generation algorithm, the Bezier curve generation algorithm, and the proposed mobile matrix algorithm are selected for comparative experiments. After completing 8 steps of fitting for each of the three algorithms, their fitting accuracy is calculated. The average fitting accuracy of the three algorithms was 83.1%, 88.7%, and 96.8%, respectively. The experimental results demonstrate that the efficiency of our proposed algorithm is nearly 40% higher than other mainstream algorithms, with an average error of 33% less.